Tax Policy and Income Inequality in the Visegrad Countries - Moździerz, Anna (Naše gospodarstvo/Our economy, 2015)
The financialisation of economies is believed to be the primary cause of the increase in income inequality in the world, occurring on a scale unseen for more than 30 years. One can hypothesise that it is the state that is responsible for the widening inequality, as the state has not sufficiently used the redistributive function of taxation. The purpose of this paper is to study the impact of tax policy on income inequality in Poland, the Czech Republic, Slovakia and Hungary. These so-called Visegrad countries have, in the last several years, carried out some controversial experiments with tax policy, specifically in terms of the flattening of tax progressivity or its replacement with a flat tax, which led to the weakening of the income adjustment mechanism. The imbalance between income tax and consumption tax has contributed to perpetuating income inequality. The verification of tax systems carried out during the recent financial crisis has forced the countries included in this research to implement tax reforms. The introduced changes caused various fiscal and redistributive effects. Analyses show that the changes in income taxation and an increase in the consumption tax rate had the most negative impact on the income and asset situation in Hungary.